Risk-taking and risk aversion in the period of before and after the 2008 crisis: evaluation with bibliometric analysis - Aren, Selim; Nayman Hamamci, Hatice (EMERALD GROUP PUBLISHING LTD, 2023)
Purpose This study aims to quantitatively classify the articles with risk-taking and risk aversion keywords and to investigate whether there is a similar emphasis in articles as parallel to the change in risk appetite in the market in the period before the crisis (bubble period) and after the crisis. Design/methodology/approach In this study, a bibliometric analysis of the articles in which the keywords risk-taking and risk aversion are mentioned together with the word finance in the journals scanned in the Web of Science between 2004 and 2012 was performed. In this context, 936 articles were specified. Analyses were made using the CiteSpace Java program. Findings The three journals with the most articles with these characteristics are Journal of Banking and Finance, Journal of Financial Economics and Strategic Management Journal. Along with these two main keywords, the other two most used keywords were model and performance. In addition, the keywords attitude, corporate governance, choice and determinant were used more in the post-crisis period. On the other hand, concepts such as investor sentiment or emotions were not amongst the 10 most frequently used keywords during the nine years. This can be considered as an indicator that risk is being modelled, but emotions are relatively neglected. As a result, the findings of this study show that academic papers do not develop in connection with the mood and excitement in the market. Originality/value This study is one of the first studies to examine the reflection of risk appetite in the market on academic papers on financial risk-taking and aversion and to investigate whether the situation in the market and the development in publications are related.
Keywords: Risk-taking; Risk aversion; Bibliometric analysis; Crisis; DECISION-MAKING; DETERMINANTS; PERCEPTION; KNOWLEDGE; BEHAVIOR; IMPACT; Business & Economics